2014
DOI: 10.1167/iovs.13-13715
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical Responses of Healthy and Keratoconic Corneas Measured Using a Noncontact Scheimpflug-Based Tonometer

Abstract: Key parameters assessed by the CST are repeatable. Keratoconus is associated with greater DA than in healthy eyes, even when controlled for CCT and IOP. Deformation amplitude may be a useful adjunct in keratoconus assessment and monitoring, but cannot solely discriminate between healthy and keratoconic corneas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
142
3
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 177 publications
(154 citation statements)
references
References 41 publications
7
142
3
2
Order By: Relevance
“…[13][14][15] The Corvis ST (Oculus Optikgeräte GmbH; Wetzlar, Germany) was later introduced as a noncontact tonometer, which monitors the response of the cornea to an air pressure pulse using an ultra-highspeed Scheimpflug camera, and uses the captured image sequence to produce estimates of IOP and deformation response parameters. 16 Several articles have recently been published on the possible applications of the Corvis ST, particularly evaluating possible biomechanical differences in the cornea after undergoing refractive surgery procedures, [17][18][19][20][21][22] between normal and keratoconic patients, [23][24][25][26] after cross-linking, 27 and in patients with glaucoma. [28][29][30][31] However, it has been demonstrated that IOP and pachymetry have important influences on most corneal biomechanical metrics provided by both the Corvis ST and ORA.…”
Section: Resultsmentioning
confidence: 99%
“…[13][14][15] The Corvis ST (Oculus Optikgeräte GmbH; Wetzlar, Germany) was later introduced as a noncontact tonometer, which monitors the response of the cornea to an air pressure pulse using an ultra-highspeed Scheimpflug camera, and uses the captured image sequence to produce estimates of IOP and deformation response parameters. 16 Several articles have recently been published on the possible applications of the Corvis ST, particularly evaluating possible biomechanical differences in the cornea after undergoing refractive surgery procedures, [17][18][19][20][21][22] between normal and keratoconic patients, [23][24][25][26] after cross-linking, 27 and in patients with glaucoma. [28][29][30][31] However, it has been demonstrated that IOP and pachymetry have important influences on most corneal biomechanical metrics provided by both the Corvis ST and ORA.…”
Section: Resultsmentioning
confidence: 99%
“…Most earlier studies produced an AUC lower than 0.900, [19][20][21] even though some of these studies refer to subclinical cases. 22 However, the dynamic Scheimpflug Corvis ST device is relatively new.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 The observation of the reduction in corneal hysteresis and corneal resistance factor values after LASIK and surface ablation has also been demonstrated. 5 This logically suggests that if CXL would significantly alter the biomechanics of progressive keratoconus corneas, these instruments would be able to identify changes.…”
Section: The Mystery Of Collagen Crosslinking When It Comes To In Vivmentioning
confidence: 93%